The biology and movement patterns of non-native common carp, cyprinus carpio (l) in Groenvlei, South Africa - Mukhari, Dinah Lorraine (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The common carp, Cyprinus carpio is a highly invasive fish species, first introduced into South Africa in the late nineteen century, and now widely spread throughout the country. In 1991 carp were illegally introduced to Groenvlei, within the Goukamma Nature Reserve in the Western Cape Province. Decreases in water quality and declines in biota have been attributed to the now large numbers of carp. Management measures have commenced to reduce the carp population, however these are not underpinned by science as little is known about the biology and movement patterns of resident carp. The age, growth and maturity of carp within the lake was determined using oxytetracycline hydrochloride marked asteriscus otoliths and macroscopic gonad development staging methods. The results showed that carp in Groenvlei had similar growth characteristics to the invasive populations in North America and Australia; fast growth during the first three to five years and reproductive maturity attained between the ages of two to three years, and are long lived (maximum age of 20 years old). Their growth however differed from the only other study on a South African population. Six acoustically tagged carp were manually tracked in order to report on their movement patterns and habitat use. Carp moved much greater distances in February compared to October and November, and occupied different areas of the lake. In November they were found to aggregate in backwaters which corresponds with their breeding activities. Literature on global carp control shows that whilst eradication of this fish can be achieved in small isolated waters using icthyocides and water drawdowns, in conservation priority areas such as Groenvlei where this is not possible, mechanical removal using multiple gears targeting vulnerable life stages can most efficient at controlling carp. This study identified where and when these methods could be focused to optimise control efforts.
Keywords: Carp -- South Africa Goukamma Nature Reserve; Introduced fishes -- South Africa Goukamma Nature Reserve; Carp Behavior -- South Africa Goukamma Nature Reserve; Carp -- South Africa Goukamma Nature Reserve Growth; Carp Habitat -- South Africa Goukamma Nature Reserve; Carp -- South Africa Goukamma Nature Reserve Reproduction; Habitat conservation -- South Africa Goukamma Nature Reserve; Aquatic resources conservation -- South Africa Goukamma Nature Reserve